2013
DOI: 10.1002/stc.1587
|View full text |Cite
|
Sign up to set email alerts
|

Isomap-based damage classification of cantilevered beam using modal frequency changes

Abstract: SUMMARY This study adopts the Isomap algorithm that uses the variation of modal frequencies caused by stiffness damage to classify damage locations in a structure. The Isomap algorithm belongs to a nonlinear generalization of classical multidimensional scaling, which makes a new coordinate system for high‐dimensional data. And this coordinate system provides good observations for the extraction of the data pattern and for the classification of their nonlinear characteristics. Thus, the Isomap can easily find g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The purpose of damage-type identification is to determine the specific type of damage present in the structure. 17,18 The damage-type identification problem, when executed through a data-driven approach, becomes a multiclass classification problem. In machine learning, there are several categories of methods for performing multiclass classification.…”
Section: Error Correcting Output Codes (Ecoc) For Damage Type Identif...mentioning
confidence: 99%
“…The purpose of damage-type identification is to determine the specific type of damage present in the structure. 17,18 The damage-type identification problem, when executed through a data-driven approach, becomes a multiclass classification problem. In machine learning, there are several categories of methods for performing multiclass classification.…”
Section: Error Correcting Output Codes (Ecoc) For Damage Type Identif...mentioning
confidence: 99%
“…Non-linear dimensionality reduction techniques became very popular in the last decade due to their superior performance on high dimensional data when compared to linear techniques [ 28 ]. Jeong [ 29 ] showed that ISOMAP outperforms PCA (a linear dimensionality reduction technique) on high dimensional data.…”
Section: Proposed Systemmentioning
confidence: 99%
“…Dimensionality reduction is very important, because it alleviates undesired properties of high-dimensional spaces, such as "the curse of dimensionality" [5]. In the literature, various dimensionality reduction methods have been proposed: (i) linear methods, such as principal component analysis (PCA) [6,7] and linear discriminant analysis (LDA) [8,9], and (ii) nonlinear methods, such as isometric mapping (ISOMAP) [10,11] and the non-parametric version of t-distributed stochastic neighbor embedding (t-SNE) [12].…”
Section: Introductionmentioning
confidence: 99%